Pengaruh Sholawat Nariyah Terhadap Kecemasan Pada Pasien Sectio Caesarea Dengan Spinal Anestesi - Suyanto Suyanto; Indri Indri; Dwi Yuliyanto (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
The percentage of caesarean section delivery rate increased from 10% from 2013 to 17% in 2018. Sectio caesarea is at risk of experiencing complications, one of which is anxiety, the level of anxiety in Sectio Caesaria patients is reported to reach 60% to 92%. One of the actions to overcome anxiety is with sholawat nariyah. Objective: to determine the effect of sholawat nariyah on anxiety in sectio caesarea patients with spinal anesthesia at Sunan Kalijaga Hospital Demak. Methods: research using Quasy Experiment with pretest-posttest control group design. The population of all sectio caesarea patients with non-probability techniques was 48 respondents. The instrument uses a questionnaire. Results: after the test, the results of sholawat nariyah have an effect on the treatment group, while in the control group there is no significant effect. The results of the analysis obtained ρ value: 0.001, if the value ρ <0.05 with a mean value of 5.00 it said that statistically there was an effect of sholawat nariyah on the level of anxiety in sectio caesarea patients with spinal anesthesia. Conclusion: there is an effect of sholawat nariyah on the level of anxiety in sectio caesarea patients with spinal anesthesia